Identifying the Need for and Availability of Evidence-Based Care for Sexually Transmitted Infections in Rural Primary Care Clinics - Merrell, Melinda A; Crouch, Elizabeth; Harrison, Sayward; Brown, Monique J; Brown, Tony; Pearson, William S (Sexually transmitted diseases, 2024)
Increasing rates of bacterial sexually transmitted infections (STIs) may lead to increased HIV rates, as the STI and HIV epidemics are syndemic. Centers for Disease Control and Prevention guidelines recommend including extragenital (i.e., rectal and/or pharyngeal) STI screenings for certain populations at increased risk of STIs and concurrent infections with HIV. A descriptive study was conducted by interviewing staff members from 4 rural primary care clinics in areas of high need for STI and HIV services in South Carolina. Qualitative data about their clinical practices in 2021 were obtained. The primary outcome was to determine the awareness and availability of health care services associated with STI and HIV care in these locations. Clinics in target counties provided limited STI and HIV testing and treatment services, especially for populations at risk of infection, indicating the need for additional clinical training and professional development for all clinic staff. Specifically, only 1 of 4 clinics provided extragenital STI testing, and no clinics reported prescribing preexposure prophylaxis. Rural primary care clinics can fill important gaps in the availability of STI and HIV services with appropriate support and incentives. Findings from this study may aid in facilitating policy (state Medicaid agency) and program (state health department) decisions related to STI and HIV testing and treatment.